2015
DOI: 10.1002/acn3.262
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of deep hypothermia in refractory status epilepticus

Abstract: ObjectivePharmacoresistance develops quickly during repetitive seizures, and refractory status epilepticus (RSE) remains a therapeutic challenge. The outcome of RSE is poor, with high mortality and morbidity. New treatments are needed. Deep hypothermia (20°C) is used clinically during reconstructive cardiac surgery and neurosurgery, and has proved safe and effective in those indications. We tested the hypothesis that deep hypothermia reduces RSE and its long‐term consequences.MethodsWe used a model of SE induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 55 publications
1
12
0
1
Order By: Relevance
“…Liu et al 24 Intraictal treatment Decreases duration Decrease 28 37-42 Maeda et al 31 Intraictal treatment Increases latency Not available 30 37 Hrncic et al 32 Intraictal treatment 100% efficacy Yes 30 37 Kowski et al 28 Intraictal treatment Relative efficacy Yes 30 a 37 Wang et al 30 Chronic epilepsy Decreases frequency Not available 30 37 Niquet et al 39 Refractory status epilepticus…”
Section: Decreases Duration Decrease 20 37mentioning
confidence: 99%
“…Liu et al 24 Intraictal treatment Decreases duration Decrease 28 37-42 Maeda et al 31 Intraictal treatment Increases latency Not available 30 37 Hrncic et al 32 Intraictal treatment 100% efficacy Yes 30 37 Kowski et al 28 Intraictal treatment Relative efficacy Yes 30 a 37 Wang et al 30 Chronic epilepsy Decreases frequency Not available 30 37 Niquet et al 39 Refractory status epilepticus…”
Section: Decreases Duration Decrease 20 37mentioning
confidence: 99%
“…Animal studies have suggested that hypothermia may have anticonvulsant effects. [32][33][34] Several case series in humans have shown the benefits of systemic hypothermia when status epilepticus is refractory to multiple anesthetic agents, [35][36][37][38] and focal cortical hypothermia has been shown to decrease epileptiform discharges. 35,39,40 These findings may account for more frequent seizures as patients reach normal body temperature.…”
Section: Frequency and Timing Of Seizuresmentioning
confidence: 99%
“…Durch eine verringerte Permeabilität der Bluthirnschranke tritt ein antiödematöser Effekt ein, zudem wirkt die Hypothermie anti-inflammatorisch. Aufgrund dieser Mechanismen wird der Hypothermie nicht nur ein antikonvulsiver, sondern auch ein neuroprotektiver Effekt zugeschrieben [42,43]. Erst kürzlich wurde der Einfluss der Hypothermie in der Statusbehandlung auf das Outcome nach 90 Tagen in der randomisierten, multizentrischen HYBERNATUS-Studie systematisch untersucht.…”
Section: Therapieunclassified